Morphological caste differences in three species of the Neotropical genus Clypearia (Hymenoptera: Polistinae: Epiponini) - Felippotti, Giovanna Tocchini; Mateus, Lucas; Mateus, Sidnei; Noll, Fernando Barbosa [UNESP]; Zucchi, Ronaldo (Wiley, 2010)
Clypearia is a rare genus of swarm-founding Neotropical wasp whose biology is very little known. Morphological castes differences, condition of ovaries, relative age, and color pattern differences were analyzed in three species of Clypearia. Physiological differences and low morphometric differentiation between queens and workers were present in all species studied, indicating that these species are characterized by physiological caste only. We suggest that caste determination in the three Clypearia species studied is postimaginal. © 2010 Giovanna Tocchini Felippotti et al.
Keywords: Epiponini; Hymenoptera; Polistinae